2016
DOI: 10.1149/2.0551605jes
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Containing Composite Coatings as a Protective Coatings against Hydrogen Embrittlement in Quenching & Partitioning High Strength Steel

Abstract: Pure Ni and Ni-graphene coatings fabricated by reverse pulse electrodeposition were applied to protect quenching & partitioning (QP) steel as the substrate from hydrogen embrittlement (HE). The inhibitory effects of coatings on HE in steel were assessed by slow strain rate test (SSRT) after electrochemical hydrogen charging and hydrogen permeation test using the Devanathan-Stachurski (D-S) cells. According to the results of the total elongation loss Elloss and steady state permeation current I∞ as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
(48 reference statements)
2
23
0
Order By: Relevance
“…In recent years, it was reported that carbon derivatives, such as carbon nanotubes (CNTs) [16][17][18], graphene (Gr) and graphene oxide (GO) [19][20][21][22][23][24][25][26][27][28][29][30][31] can be used as anti-corrosion additives to organic coatings. Gr has attracted considerable attention owing to its extraordinary electrical and physical properties, especially its impermeable nature [32][33][34]. There are a number of studies showing that adding Gr and its derivatives to a polymer coating can enhance the corrosion performance of the coating [19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it was reported that carbon derivatives, such as carbon nanotubes (CNTs) [16][17][18], graphene (Gr) and graphene oxide (GO) [19][20][21][22][23][24][25][26][27][28][29][30][31] can be used as anti-corrosion additives to organic coatings. Gr has attracted considerable attention owing to its extraordinary electrical and physical properties, especially its impermeable nature [32][33][34]. There are a number of studies showing that adding Gr and its derivatives to a polymer coating can enhance the corrosion performance of the coating [19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…To study the hydrogen permeation resistance of the MXene coatings, hydrogen permeation tests were performed with the aid of the Devanathan-Stachurski (D-S) cell [ 20 ] in which aqueous saturated calomel electrode (SCE) was the reference electrode, platinum foil was the counter electrode, and 0.2 mol/L NaOH was the electrolyte. Before the hydrogen permeation test was performed, a layer of nickel was plated on the uncoated side of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown that graphene is impermeable to atomic hydrogen [36][37][38]. Therefore, the 3DIGN in 3Di Gr-Cu composite can function as an effective barrier to atomic hydrogen.…”
Section: Hydrogen-assisted Corrosion (Hac)mentioning
confidence: 99%